Staying Egalitarian and the Origins of Agriculture in the Middle East. Issue 4 (November 2022) - Hodder, Ian
Abstract : This article uses results from the recent excavations at Çatalhöyük in Turkey to propose that continuous tensions between egalitarian and hierarchical impulses were dealt with in two principal ways during the Neolithic of the Middle East. A tendency towards overall balance and community (termed molar) is seen as in tension with more particulate and molecular tendencies, with both being brought into play in order to combat inequalities. It is also suggested that tendencies towards more molecular systems increased over time, at different rates and in different ways in different places, partly as a response to constraints associated with more molar articulations. Finally, it is proposed that a shift to molecular autonomy was associated with agricultural intensification. Staying egalitarian can be seen as an active process that contributed to the Neolithic transformations.